Factors influencing the integration of non-timber forest products into field crop cultivation: a case study from Eastern Nepal - Pandit, B.H. (2010)
This article examines the feasibility of integrating five non-timber forest product (NTFP) species into field crop cultivation in eastern Nepal. Cost-benefit analyses including Net Present Value (NPV) and Benefit-Cost Ratio (BCR) show that all the NTFP species are more profitable than field crops. This profitability relationship holds true even under a sensitivity analysis assuming a 20% reduction in yield and/or fall in prices. However, despite the profitability, farmers do not readily integrate these species into their farmlands on a large scale. A regression analysis of constraining factors explored in a household survey revealed that domestication of NTFP species is significantly influenced by factors such as knowledge and skill required for domestication, frequency of visits to a forest, length of fallow period, size of upland terraces, cattle and goat herd size, accessibility of a forest, permit system, trading system, and market uncertainty. Overall, the unfavorable institutional environment has been the major factor constraining the integration of NTFP species into farmland. Policy recommendations include transferring management to local people such as changing the open-access status of national forests; providing NTFP collection permits to local residents; amending inappropriate policies; promoting group marketing; and taking an adaptive, collaborative approach to community forestry.